Notopterol Attenuates Estrogen Deficiency-Induced Osteoporosis via Repressing RANKL Signaling and Reactive Oxygen Species - Chen, Delong; Wang, Qingqing; Li, Ying; Sun, Ping; Kuek, Vincent; Yuan, Jinbo; Yang, Junzheng; Wen, Longfei; Wang, Haibin; Xu, Jiake; Chen, Peng (Frontiers in Pharmacology, 2021)
Integrity of the skeleton is sustained through the balanced activities of osteoblasts and osteoclasts in bone remodeling unit. The balance can be disrupted by excessive osteoclasts activation commonly seen in osteoporosis. Notopterol (NOT) is a main component of Notopterygium incisum which exerts a wide spectrum effect on biomedical pharmacology. In our study, we found NOT serves as an inhibitor in regulating RANKL-activated osteoclasts formation and bone resorption function by calculating tartrate resistant acid phosphatase (TRAcP) staining and hydroxyapatite resorption assays. Furthermore, RANKL-mediated signaling pathways including MAPK, NF-κB and calcium ossification were hampered, whereas ROS scavenging enzymes in Nrf2 / Keap1/ ARE signaling pathways were promoted by NOT. In addition, the activation of the essential transcription factor NFATc1 in RANKL-mediated osteoclastogenesis was almost totally suppressed by NOT. What is more, NOT diminished the loss of bone mass in preclinical model of OVX mice by blocking osteoclastogenesis determined by bone histomorphometry, TRAcP staining and H&E staining. Conclusively, our findings demonstrated that NOT could arrest osteoclastogenesis and bone resorptive activity by attenuating RANKL-mediated MAPK, NF-κB, calcium and NFATc1 signaling transduction pathways and enhancing ROS scavenging enzymes in Nrf2/Keap1/ARE pathways in vitro, and prohibit bone loss induced by OVX in vivo. Taken together, NOT may be identified to be a natural and novel treatment for osteolytic diseases.